KOMUNIKASI BUDAYA MELALUI PROSESI PERKAWINAN ADAT PADA SUKU BATAK TOBA - Novelita, Ruth; Luthfie, Muhammad; Fitriah, Maria (JURNAL KOMUNIKATIO, 2019)
Customary marriage procession in the Toba Batak tribe is a process that is carried out repeatedly. In the process of the traditional marriage of the Batak tribe there are several stages that must be passed to achieve a Batak community's recognition of the marriage. This study aims to analyze the communication process that occurs in the traditional marriage of the Batak Toba tribe. The research approach used is qualitative with descriptive method. Data collection is done by observation techniques, in-depth interviews, and documentation studies. The data analysis technique uses Miles and Huberman theories, namely data reduction, data presentation, and conclusion drawing. To check and compare the validity of the data using the source triangulation analysis technique.The results of the study show that the Batak culture community has high values of customs in the marriage of the Toba Batak tribe. This conclusion is evidenced that in the modern era, Batak culture communities still use traditional processes such as the process of marhatasinamot, and the process of mangulosi in the marriage of Batak culture. Â Keywords: Cultural Communication; Traditional Ceremonies; Wedding Procession.